# Solve for y 0.27-(7-2y)=2.3-0.3(y-6) 0.27-(7-2y)=2.3-0.3(y-6)
Simplify 0.27-(7-2y).
Simplify each term.
Apply the distributive property.
0.27-1⋅7-(-2y)=2.3-0.3(y-6)
Multiply -1 by 7.
0.27-7-(-2y)=2.3-0.3(y-6)
Multiply -2 by -1.
0.27-7+2y=2.3-0.3(y-6)
0.27-7+2y=2.3-0.3(y-6)
Subtract 7 from 0.27.
-6.73+2y=2.3-0.3(y-6)
-6.73+2y=2.3-0.3(y-6)
Simplify 2.3-0.3(y-6).
Simplify each term.
Apply the distributive property.
-6.73+2y=2.3-0.3y-0.3⋅-6
Multiply -0.3 by -6.
-6.73+2y=2.3-0.3y+1.8
-6.73+2y=2.3-0.3y+1.8
Add 2.3 and 1.8.
-6.73+2y=-0.3y+4.1
-6.73+2y=-0.3y+4.1
Move all terms containing y to the left side of the equation.
Add 0.3y to both sides of the equation.
-6.73+2y+0.3y=4.1
Add 2y and 0.3y.
-6.73+2.3y=4.1
-6.73+2.3y=4.1
Move all terms not containing y to the right side of the equation.
Add 6.73 to both sides of the equation.
2.3y=4.1+6.73
Add 4.1 and 6.73.
2.3y=10.83
2.3y=10.83
Divide each term by 2.3 and simplify.
Divide each term in 2.3y=10.83 by 2.3.
2.3y2.3=10.832.3
Cancel the common factor of 2.3.
y=10.832.3
Divide 10.83 by 2.3.
y=4.70869565
y=4.70869565
Solve for y 0.27-(7-2y)=2.3-0.3(y-6)

### Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top